2021
DOI: 10.1177/17562864211023992
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intraplaque neovascularisation as a predictive factor for future vascular events in patients with mild and moderate carotid stenosis: an observational prospective study

Abstract: Background: Intraplaque neovascularisation (IPN) increases the vulnerability of plaques, which makes them more likely to rupture and increases the risk of vascular events. However, it is unclear whether IPN can predict future vascular events (stroke recurrence and cardiovascular events). Previous studies on IPN have focused on patients with severe stenosis but overlooked patients with mild and moderate stenosis. This study aimed to investigate whether IPN assessed by contrast-enhanced ultrasonography (CEUS) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Furthermore, the median stenosis rate of CaW patients was 40% (IQR, 30–50%). Patients with mild to moderate stenosis were at an increased risk of future vascular events ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the median stenosis rate of CaW patients was 40% (IQR, 30–50%). Patients with mild to moderate stenosis were at an increased risk of future vascular events ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Raw images were stored in the scanner’s hard drive for offline analysis. Routine carotid ultrasonography and CEUS examination were performed as previously described ( Cui et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it was shown in a meta-analysis that the prevalence of IPN was higher in SCS compared with ACS patients [15] and correlates with cardiovascular events [61]. Different prospective studies also demonstrated that in patients with a recent ischemic cerebrovascular event the risk of future ischemic stroke or TIA was significantly associated with IPN in carotid CEUS examination [62,63]. IPN on CEUS imaging was also found to be predictive of significant and complex coronary artery disease and future cardiovascular events [64].…”
Section: Impact Of Contrast Materialsmentioning
confidence: 98%